A modified VDVTA and its applications to floating simulators and a quadrature oscillator. (May 2016) - Alpaslan, Halil
Abstract: In this paper, a modified voltage differencing voltage transconductance amplifier (MVDVTA) is proposed. A single MVDVTA based three circuits with a minimum number of only grounded passive components which are suitable for integrated circuit (IC) design are also proposed. The first circuit can realize lossless positive and negative floating inductor (FI), floating capacitor (FC) and floating resistor (FR) depending on the passive component selection. The second one is a floating frequency-dependent negative resistor (FFDNR) simulator. The third one is a quadrature oscillator (QO) with oscillation condition. The floating simulators are independent of passive component matching and/or cancellation conditions. Simulation results obtained from SPICE program and an experimental test result are given to verify the theory. In all the simulations, IBM CMOS 0.13 µm process parameters are used.